Simulation-Based Case Studies in Logistics Education and Applied Research - Merkuryev, Yuri.; Merkuryeva, Galina.; Piera, Miquel °ngel.; Guasch, Antoni. (Springer London, 2009)
Simulation-based Case Studies in Logistics presents an intensive learning course on the application of simulation as a decision support tool to tackle complex logistic problems. The book describes and illustrates different approaches to developing simulation models at the right abstraction level to be used efficiently by engineers when dealing with strategic, tactical or operational decisions in logistic systems. 11 simulation-based case studies in logistics and supply chain management are discussed, based on the results of applied research, covering application areas such as production logistics, warehousing, transportation, material flow management, and hospital logistics. Simulation-based Case Studies in Logistics is an essential text for postgraduate engineering students and researchers working in the area of logistics modeling and simulation.